SYSTEM REGULARITY OF MECHANICS AND ROTOR BALANCING - Oleg O. Polushkin (Advanced Engineering Research)
New results of the rotor dynamics fundamental research are presented. These results permit to realize the system approach to the rotor balancing at all stages of the creation and operation of the omni-purpose machines. The results implementation is exemplified.